'We are expected to be problem solvers'-Paramedics' performance expectations through the lens of organizational socialization: An interview study - Christoffer R. Ericsson; Ann Rudman; Veronica Lindström; Hilla Nordquist (Wiley, 2024)
Abstract Aim To explore Finnish paramedics' perceptions of work‐related performance expectations in relation to work experience, and understand how organizational socialization contributes to understanding paramedics' performance expectations. Design A qualitative design with a deductive‐inductive approach utilizing a social constructivist framework. The organizational socialization framework by Wanberg was used as the theoretical basis. Methods Data were collected between May and August 2023, using group and individual interviews of newly graduated (n = 9) and experienced paramedics (n = 13). Participants were recruited via social media channels. Data were first analyzed deductively, according to constructs of the organizational socialization framework (role clarity, task mastery, and social acceptance), then inductively, using codes not utilized in the deductive phase. Data Sources Interviewed Finnish paramedics (N = 22), both newly graduated paramedics (n = 9) and experienced paramedics (n = 13). The interviews were performed remotely and then transcribed into text. Results Our findings showed comparable performance expectations between newly graduated and experienced paramedics, mismatches in role clarity of paramedic work, challenges in both learning and upholding professional competence, and difficulties of social acceptance into the paramedic community. There were variations in how expectations were perceived between groups, indicating that experience might partly affect how paramedics identify and manage performance expectations. The organizational socialization framework enables the contextualization of these performance expectations. Conclusions and Implications Paramedic work involves challenges to upholding clinical competence, aligning to a professional role, and social integration into the professional community. Our research contributes to understanding how paramedics perceive these challenges as performance expectations in different stages of their careers and how they could be managed utilizing a framework for organizational socialization. The socialization of paramedics into the workforce needs to account for these performance expectations, especially considering the changing paradigm of paramedic work, role, and societal expectations. Patient or Public Contribution No Patient or Public Contribution.